Influence of drill bit diameter on drilling of polyurethane foams - Teixeira, T.T. (2018)
Drilling is one of the most common processes involved in machining operations The usual requirement is the efficient material removal. However, when it comes to the living tissues, drilling assumes greater attention to ensure a minimally invasive procedure.